Reseña/Review (Urry, John, "Mobilities", Oxford: Polity Press, ISBN: 9780745634197, 326 págs., 2007) - Pompeyo, César (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2011)
Reseña/Review (Urry, John, "Mobilities", Oxford: Polity Press, ISBN: 9780745634197, 326 págs., 2007)